Bahasa Inggris - Datau, Fadhilah; Arpin; Mindy Eka Astuti (Journal of Health, Technology and Science (JHTS), 2023)
This study aims to determine the results of examination of endoparasite worms in beef at the Gorontalo City Slaughterhouse and to determine the factors that influence the presence of endoparasite worms in beef at the Gorontalo City Slaughterhouse.This research method uses a quantitative research approach with the type of research used in this research is descriptive observational research. The population in this study was all sirloin meat in the Gorontalo City Slaughterhouse, amounting to 20. The sample used was 12 with the sampling technique using Accidental Sampling.The results of this study showed that 12 samples were positively infected with endoparasite worms with a percentage (100%). Types of endoparasitic worms found included 2 species of Fasciola hepatica, 1 species of Strongyloides papillosus, 1 species of Paramphistomum, 1 species of Trichostrongylus, 1 species of Bunostomum, 1 species of Cooperia, 1 species of Strongyloides stercoralis, 1 species of Toxocara vitulorum, 1 species of Haemonchus contortus, Oesophagustomum 2 types.